Ramucirumab as second-line treatment in patients with advanced hepatocellular carcinoma following first-line therapy with sorafenib: Patient-focused outcome results from the randomised phase III REACH study. (August 2017) - Chau, Ian; Peck-Radosavljevic, Markus; Borg, Christophe; Malfertheiner, Peter; Seitz, Jean Francois; Park, Joon Oh; Ryoo, Baek-Yeol; Yen, Chia-Jui; Kudo, Masatoshi; Poon, Ronnie; Pastorelli, Davide; Blanc, Jean-Frederic; et al.
Abstract: Purpose: To report patient-focused outcomes as measured by quality of life (QoL) and performance status (PS) in REACH, a phase III placebo-controlled randomised study, assessing ramucirumab in advanced hepatocellular carcinoma (HCC) patients who received prior sorafenib. Methods: Eligible patients had advanced HCC, Child-Pugh A, PS 0 or 1 and prior sorafenib. Patients received ramucirumab (8 mg/kg) or placebo (1:1) on day 1 of a 2-week cycle. QoL was assessed by FACT Hepatobiliary Symptom Index (FHSI)-8 and EuroQoL (EQ-5D) at baseline; cycles 4, 10, and 16; and end of treatment. PS was assessed at baseline, each cycle, and end of treatment. Deterioration in FHSI-8 was defined as a ≥3-point decrease from baseline and PS deterioration was defined as a change of ≥2. Both intention-to-treat and pre-specified subgroup of patients with baseline serum alpha-fetoprotein (AFP) ≥400 ng/mL were assessed. Results: There were 565 patients randomised to ramucirumab and placebo. Compliance with FHSI and EQ-5D was high and similar between groups. In the ITT population, deterioration in FHSI-8, EQ-5D, and PS was similar between ramucirumab and placebo. In patients with baseline AFP ≥400 ng/mL, ramucirumab significantly reduced deterioration in FHSI-8 at the end of treatment compared with placebo ( P  = 0.0381), and there was a trend towards a delay in the deterioration of symptoms in FHSI-8 (HR 0.690; P  = 0.054) and PS (HR 0.642; P  = 0.057) in favour of ramucirumab. Conclusions: We report one of the most comprehensive data sets of QoL and symptom burden in patients undergoing systemic therapy for advanced HCC. Ramucirumab was associated with no worsening of QoL. In patients with baseline AFP ≥400 ng/mL, the significant survival benefit observed in patients treated with ramucirumab was coupled with a trend in patient-focused outcome benefits. Clinical trial registration: NCT01140347 . Highlights: We report patient-focused outcomes as measured by quality of life (QoL) and performance status (PS) in REACH. Ramucirumab significantly reduced deterioration in QoL in subgroup with baseline high alpha fetoprotein. There was also a trend towards delaying deterioration of QoL and PS in favour of ramucirumab. Significant survival benefit coupled with a trend in patient-focused outcome benefits was observed with ramucirumab. We reported one of the most comprehensive datasets of QoL and symptom burden in systemic therapy for advanced HCC.